89 Mr. (12th November 2018) - Hughes, Will; Maheswaran, Tim; Thayaparan, Anthony; Saavedra, Enrique
Abstract : Consent is a vital two way process between clinician and patient, and done well, ensures that patients are able to make informed decisions about their care. A quality improvement project was designed to improve consenting at Central Middlesex Hospital. A 6 week prospective audit of the consent taken for Total Knee Replacements (TKRs) and Knee Arthroscopies (KA) was performed. The consent forms for these procedures were analysed for the risks documented, the legibility and whether alternatives to surgery were discussed and documented. In total 15 KAs and 21TKRs were reviewed. The risks documented were compared to a standard taken from www.OrthoConsent.com (OrthoConsent) – a website endorsed by the British Orthopaedic Association. From this website, 12 risks were identified for TKRs, and 7 for KAs. Our data identified that on average, just over half of the risks for TKRs were consented (53%), and slightly more than two thirds consented for KAs (68%). The legibility of the hand-written forms was graded on a scale of 1; illegible, 2; legible, and 3; printed, with majority being graded as 2. No alternatives to surgery were discussed during consent. The intervention used by our group was to print consent forms from OrthoConsent and use them alongside the hand-written forms. We re-audited for 6 weeks. The information is provided on a printed form, with alternatives to surgery included, the results of the re-audit showed 100% of the risks being documented, all consent forms being printed and legible (level 3 on the scale), and alternatives being discussed. We demonstrated leadership skills in identifying a problem, investigating it and providing a solution to an important problem: consent. The results of our project have been communicated to members of our Trust and department with a view to implementing this to the wider practice.